Strategi Perguruan Tinggi Mencetak Wirausaha Muda: (Studi Kasus STIE Ganesha) - Azizah Musyafia; Aep Saefullah; Ekky Noviar; Novitara Anggraeni; Zahra Widdatul Awwaliyah; Lusi Fitriyani; Nurdin Nurdin (Jurnal Kajian dan Penelitian Umum, 2024)
To become an entrepreneur, strategies are needed in order to become a successful entrepreneur. In this study, STIE Ganesha's strategy in creating young entrepreneurs is by establishing the Ganesha Laboratory Entrepreneur (GLP) Institute, in accordance with the vision of STIE Ganesha itself, namely creating students and graduates of STIE Ganesha who have entrepreneurial character. The research method used is qualitative research with data collection techniques through interviews and observations. Researchers interviewed lecturers and students at STIE Ganesha. The results of the study state that STIE Ganesha has so far helped its students to become young entrepreneurs, namely by holding webinars or workshops for students, including students in the P2MW programme, holding mini expos of food made by students, and forming an Entrepreneurial Student Association (HIMARA). Therefore, universities are a place for students to start a new or ongoing business.